Comparing the effect of solution-focused therapy and structural family therapy on marital satisfaction and family function in married women - Seyyedmoharrami, Iman; Ghanbari HashemAbadi, Bahramali; Asghari EbrahimAbad, Mohammad Javad; Zandi, Anahita (Social Determinants of Health, 2022)
Background: Marital satisfaction is a situation in which couples can feel happiness and satisfaction with each other. Recently, various therapy techniques have been developed to solve marital and family problems. The purpose of the study was to comparing the effects of group counseling based on solution-focused therapy and structural family therapy (SFT) on the marital satisfaction and family function among married women. Material and Methods: This interventional study was performed in three of groups married women (20 people as cases in two groups and 10 people as control group). The research population included of all married females referred to the Faculty of Education and Psychology clinic, at Ferdowsi University of Mashhad in Iran. The instruments for data collection in this study were marital satisfaction scale (MSS) and the family function scale (FFS). Data analysis was done using SPSS 21 software and the analysis of covariance, and LSD post-hoc test were employed. Results: The findings revealed that there is no meaningful difference among married females who received SFT and solution-focused therapy (p>0.05); However structural family and solution-focused of group counseling compared with the control group had significant difference in the influence on family function and marital satisfaction (P=0.014 and P=0.024, respectively). Conclusions: Based on the results, solution-focused group counseling had more effective than structural group counseling in improving family function and marital satisfaction.